Bridging the experience gap: cognitive biases and heuristics in the internationalization of small firms - Faroque, Anisur R.; Casulli, Lucrezia; Kuivalainen, Olli; Sundqvist, Sanna (Emerald, 2025)
Purpose Research on early internationalization in smaller firms has primarily focused on initial market entry, often neglecting responses to adverse post-entry events. This paper addresses the gap between entrepreneurial internationalization and small business survival by examining both initial and post-entry stages through decision-maker cognition. Design/methodology/approach This conceptual paper develops a cognition-based decision framework that explains how cognitive biases influence pre- and initial entry decisions, and evolve in response to post-entry negative events. It introduces the “experience gap paradox”- a misalignment between personal experience and required international market experience – as a key driver of biased judgment. The framework links non-contextualized pre-entry experience with post-entry decision-making, offering testable propositions on the dynamic interplay between biases, heuristics, and internationalization decisions. Findings This model supports the argument that heuristic decision-making is contingent upon context-specific prior experience, which leaders of small firms typically lack pre-entry, causing them to develop and rely on decision biases. Originality/value This article contributes by exploring how cognitive heuristics and biases evolve in decision-making across the pre-entry and post-entry stages of internationalization, with a focus on smaller firms-particularly International New Ventures (INVs). It provides a comprehensive understanding of the “experience gap paradox” and its influence on entrepreneurial internationalization, offering insights relevant to small firms' adaptive decision-making and survival.
Keywords: Early internationalization; Small firms; Decision-maker cognition; Experience gap paradox; Evolution of cognitive biases; Heuristics; fi=Kansainvälinen liiketoiminta|en=International Business|